Implementation of Process Standards Through Supervision and Monitoring in Nonformal Education at PKBM Cahaya Ilmu Pekanbaru - Patricia Romasta Hutabalian; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the implementation of process standards through supervision and monitoring in non-formal education programs at PKBM Cahaya Ilmu Pekanbaru. Process standards serve as quality benchmarks that must be met in the delivery of education, including on the non-formal pathway. Supervision and monitoring are two managerial instruments that ensure the consistent implementation of process standards. This research employed a descriptive qualitative approach, collecting data through field observation, in-depth interviews with the institution's administrators and three tutors of equivalency programs (Paket A, B, and C), and institutional documentation. Data were analyzed using the Miles and Huberman model through data reduction, presentation, and conclusion drawing. Source and method triangulation were applied to ensure data validity. The results indicate that PKBM Cahaya Ilmu has implemented periodic supervision at the end of each semester through a collaborative coaching and professional reflection approach. Monitoring was carried out by tracking learner attendance, module achievement, and the effectiveness of learning strategies. Supervision contributed to improving tutors' pedagogical competence, while monitoring functioned as a quality control mechanism for the program. Major challenges included limited human resources, tutor time constraints, and irregular learner attendance. The study recommends strengthening a digital-based supervision and monitoring system to enhance efficiency and ensure systematic documentation.